2001
DOI: 10.1046/j.1442-2042.2001.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

New concept parameters of RigiScan in differentiation of vascular erectile dysfunction: Is it a useful test?

Abstract: New recording parameters of nocturnal penile tumescence can differentiate organic and psychogenic erectile dysfunction more precisely. However, these recording parameters cannot distinguish subgroups with a vascular cause of erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
1
21
1
1
Order By: Relevance
“…Various studies undertaken in different decades revealed that NPTR has an important role in the differentiation of well-known organic impotence from psychogenic impotence but is insufficient in identifying the underlying cause of organic impotence. 18,25,26 Hence, our result that the potential vascular lesion EnD presented in ED patients with normal NPTR support the conclusion in previous literature study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Various studies undertaken in different decades revealed that NPTR has an important role in the differentiation of well-known organic impotence from psychogenic impotence but is insufficient in identifying the underlying cause of organic impotence. 18,25,26 Hence, our result that the potential vascular lesion EnD presented in ED patients with normal NPTR support the conclusion in previous literature study.…”
Section: Discussionsupporting
confidence: 92%
“…It is suggested that NPTR recording is recommended when a psychogenic etiology is suggested by the sexual history, and there are no neurovascular risk factors present. 24,25 A man with ED but no obvious risk factors, having a normal NPTR recording with three to five erectile events, lasting more than 10 min with tip rigidity more than 60--70%, can be safely diagnosed with a psychogenic etiology. 18 However, after excluding cardiovascular risks, no statistical differences were found in NPTR parameters between non-EnD and EnD ED in the psychogenic group (P40.05).…”
Section: Discussionmentioning
confidence: 99%
“…Number of events, total events duration (in hours), average rigidity of tip and base, and RAU and TAU were determined. 7 To avoid, or at least minimize the effect of adaptation, patients were randomly divided into two groups, evaluation of NPTR has been extended to four consecutive nights and sildenafil citrate has been administered on a different night in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, though a recent survey suggests that its use as a diagnostic test occurs in only some 3-4% of cases, 2 NPT with RigiScan remains the gold standard in assessing penile rigidity. DDU allows for the evaluation of penile cavernosal blood vessels (Duplex) and blood flow (Doppler) in conjunction with vaso-dilator stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the patients with a vascular cause, no difference was found between arterial and veno-occlusive dysfunction with regard to tip tumescence activity unit (TAU), base TAU, tip rigidity activity unit (RAU), base RAU and erection time. 2 A thorough clinical assessment alongside the patient's own description of their erectile status should be sufficient. A study looking at the predictive value of the patients' own subjective assessment of early morning and nocturnal erections and the presence of vascular risk factors and cigarette smoking correlated well with the outcome of RigiScan and PSV (peak systolic velocity) during colour flow duplex Doppler ultrasonography.…”
Section: Introductionmentioning
confidence: 99%